Vibration Analysis of Non-Metallic Materials - Sriraman, Shabarish (Cranfield University, 2022)
A 3MT talk on developing a hybrid method, which combines experimental testing and simulation tuning, to characterise the dynamic vibration properties of materials. Topics discussed include: - Why we need a new characterisation method - How the method works - Capability and key innovation, including a new approach to damping and reducing estimations in simulations - Validation and results
Keywords: Vibration of Materials'; 'Hybrid Method'; 'High Frequency Range & Temperature Testing'; 'DSDS21'; 'DSDS21 3MT'; 'Dynamics; Vibration and Vibration Control'